Tri-ponderal mass index vs. Fat mass/height3 as a screening tool for metabolic syndrome prediction in colombian children and young people (2018)
Tri-ponderal mass index (TMI) and Fat mass index (FMI) have been proposed as alternative approach for assessing body fat since BMI does not ensure an accurate screening for obesity and overweight status in children and adolescents. This study proposes thresholds of the TMI and FMI for the prediction of metabolic syndrome (MetS) in children and young people. For this purpose, a cross-sectional study was conducted on 4,673 participants (57.1% females), who were 9–25 years of age. As part of the study, measurements were taken of the subjects’ weight, waist circumference, serum lipid indices, blood pressure and fasting plasma glucose. Body composition was measured by bioelectrical impedance analysis (BIA). The TMI and FMI were calculated as weight (kg)/height (m3) and fat mass (kg)/height (m3), respectively. Following the international diabetes federation definition, MetS was defined as including three or more metabolic abnormalities. Cohort-specific thresholds were established to identify Colombian children and young people at high risk of MetS. The thresholds were applied to the following groups, including: (i) cohort of children with TMI ≥ 12.13 kg/m3 (girls) and ≥ 12.10 kg/m3 (boys); (ii) cohort of adolescents with TMI ≥ 12.48 kg/m3 (girls) and ≥ 11.19 kg/m3 (boys); and (iii) cohort of young adults with TMI ≥ 13.21 kg/m3 (women) and ≥ 12.19 kg/m3 (men). The FMI reference cut-off values used were as follows for the different groups, including: (i) cohort of children with FMI ≥ 2.59 fat mass/m3 (girls) and ≥ 1.98 fat mass/m3 (boys); (ii) cohort of adolescents with FMI ≥ 3.12 fat mass/m3 (girls) and ≥ 1.46 fat mass/m3 (boys); and (iii) cohort of adults with FMI ≥ 3.27 kg/m3 (women) and ≥ 1.65 kg/m3 (men). Our results showed that the FMI and TMI had a moderate discriminatory power to detect MetS in Colombian children, adolescents and young adults. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.